Rise of the rocket girls : the women who propelled us, from missiles to the moon to Mars - Holt, Nathalia (New York : Little, Brown and Company, 2016)
"During World War II, when the newly minted Jet Propulsion Laboratory needed quick-thinking mathematicians to calculate jet velocities and plot missile trajectories, they recruited an elite group of young women--known as human computers--who, with only pencil, paper, and mathematical prowess, transformed rocket design and helped bring about America's first ballistic missiles. But they were never interested in developing weapons--their hearts lay in the dream of space exploration. So when JPL became part of a new agency called NASA, the computers worked on the first probes to the moon, Venus, Mars, and beyond. Later, as digital computers largely replaced human ones, JPL was unique in training and retaining its brilliant pool of women. They became the first computer programmers and engineers, and through their efforts, we launched the ships that showed us the contours of our solar system. For the first time, Rise of the Rocket Girls tells the stories of these women who charted a course not only for the future of space exploration but also for the prospects of female scientists. Based on extensive research and interviews with the living members of the team, Rise of the Rocket Girls offers a unique perspective on the role of women in science, illuminating both where we've been and the far reaches of space to where we're heading."--Dust jacket.
January 1958 : Launch day -- Part I. 1940s. Up, up, and away -- Headed west -- Part II. 1950s. Rockets rising -- Miss Guided Missile -- Holding back -- Ninety days and ninety minutes -- Moonglow -- Part III. 1960s. Analog overlords -- Planetary pull -- The last queen of outer space -- Part IV. 1970s-today. Men are from Mars -- Look like a girl -- Epilogue.
Includes bibliographical references (pages 293-323) and index.
Keywords: Jet Propulsion Laboratory (U.S.) -- Biography; Jet Propulsion Laboratory (U.S.) -- History; Women mathematicians -- United States -- Biography; Women computer scientists -- United States -- Biography; Women computer programmers -- United States -- Biography; Women mathematicians -- United States -- History; Women computer programmers -- United States -- History; Rocketry -- United States -- History -- 20th century. -- Biography; Astronautics -- United States -- History -- 20th century